1973
DOI: 10.1063/1.1662297
|View full text |Cite
|
Sign up to set email alerts
|

Internal stresses and resistivity of low-voltage sputtered tungsten films

Abstract: The continuing development of microelectronic circuits toward greater complexity has stimulated interest in new materials and processes compatible with the currently known silicon device technology. Tungsten has been considered as the first-level conductor for a multilevel structure due to its relatively low electrical resistivity, its thermal expansion coefficient which matches fairly well to that of silicon, its demonstrated good adherence to the dielectrics of interest, and its ability to withstand high-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…[6][7][8] During sputtering deposition on a biased substrate, the deposited MoW film is subjected to ion bombardment by highly energized ions and these ions can produce ion-radiated defects such as dislocation loops and point defects. 2 and 4 is that the biased tungsten-rich alloy has a higher resistivity than biased molybdenum-rich alloy, ͑c͒ and ͑d͒.…”
Section: B Films Deposited With Negative Bias "30 W −165 V… At Roomentioning
confidence: 99%
“…[6][7][8] During sputtering deposition on a biased substrate, the deposited MoW film is subjected to ion bombardment by highly energized ions and these ions can produce ion-radiated defects such as dislocation loops and point defects. 2 and 4 is that the biased tungsten-rich alloy has a higher resistivity than biased molybdenum-rich alloy, ͑c͒ and ͑d͒.…”
Section: B Films Deposited With Negative Bias "30 W −165 V… At Roomentioning
confidence: 99%
“…After 5 minutes of annealing at 850°C or 1000°C the complete interdiffusion of Si in the W layer takes place, as shown in Figure 6. Correspondingly, the values for decrease by almost one additional order of magnitude if compared with W annealed at 450°C, reaching  4•10 -4 Ω•cm 2 . Table 1 reports a comparison of the experimental values obtained in this work with those featured by direct ohmic W/Si contacts fabricated using several deposition techniques, with and without thermal annealing process.…”
Section: The Values Formentioning
confidence: 93%
“…Tungsten is used in microelectronics since decades, to provide metallic contact on Si and wide band-gap semiconductors such as silicon carbide [1][2][3][4]. It features complementary metal oxide semiconductor compatibility, a high melting temperature, useful to sustain the chemical vapor deposition (CVD) processes typical of very large-scale integration (VLSI) technology and to guarantee the thermal stability of the contact, high mechanical and chemical resistance as well as high adhesion and wettability on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Stronger and sharper (110) and (200) tungsten peaks appeared in CVD layer in x-ray diffraction spectra. It has been reported that much greater grain size could be achieved in the CVD layer when compared with the sputtered layer (8,15,16).…”
Section: Impurity Concentration Profile In High Concentrationmentioning
confidence: 99%